Water‐use advantage for lianas over trees in tropical seasonal forests - Chen, Ya‐Jun; Cao, Kun‐Fang; Schnitzer, Stefan A; Fan, Ze‐Xin; Zhang, Jiao‐Lin; Bongers, Frans (The New phytologist, 2015)
Lianas exhibit peak abundance in tropical forests with strong seasonal droughts, the eco‐physiological mechanisms associated with lianas coping with water deficits are poorly understood. We examined soil water partitioning, sap flow, and canopy eco‐physiological properties for 99 individuals of 15 liana and 34 co‐occurring tree species in three tropical forests that differed in soil water availability. In the dry season, lianas used a higher proportion of deep soil water in the karst forest (KF; an area with severe seasonal soil water deficit (SSWD)) and in the tropical seasonal forest (TSF, moderate SSWD), permitting them to maintain a comparable leaf water status than trees in the TSF or a better status than trees in the KF. Lianas exhibited strong stomatal control to maximize carbon fixation while minimizing dry season water loss. During the dry period, lianas significantly decreased water consumption in the TSF and the KF. Additionally, lianas had a much higher maximum photosynthetic rates and sap flux density in the wet season and a lower proportional decline in photosynthesis in the dry season compared with those of trees. Our results indicated that access to deep soil water and strong physiological adjustments in the dry season together with active wet‐season photosynthesis may explain the high abundance of lianas in seasonally dry forests.